Step
*
of Lemma
sub-bag-append-trivial2
∀[T:Type]. ∀[b,y:bag(T)].  ∀x:bag(T). (sub-bag(T;b;y) 
⇒ sub-bag(T;b;x + y))
BY
{ (Auto
   THEN All (Unfold `sub-bag`)
   THEN ExRepD
   THEN (InstConcl [⌜x + cs⌝]⋅ THENA Auto)
   THEN HypSubst' (-1) 0
   THEN Auto) }
Latex:
Latex:
\mforall{}[T:Type].  \mforall{}[b,y:bag(T)].    \mforall{}x:bag(T).  (sub-bag(T;b;y)  {}\mRightarrow{}  sub-bag(T;b;x  +  y))
By
Latex:
(Auto
  THEN  All  (Unfold  `sub-bag`)
  THEN  ExRepD
  THEN  (InstConcl  [\mkleeneopen{}x  +  cs\mkleeneclose{}]\mcdot{}  THENA  Auto)
  THEN  HypSubst'  (-1)  0
  THEN  Auto)
Home
Index